The feminist clowning of the Circo di SóLadies | Nem SóLadies (Urdimento: Revista de Estudos em Artes Cênicas, 2023)
Circo di SóLadies | Nem SóLadies is a group of clowns that usually bring, in their dramaturgies, realities and themes related to the universe of women, non-binary people, and those who are considered dissident bodies, those note privileged by the patriarchy. They call themselves feminist clowning makers, neglecting the term feminine. The group discusses their training paths, the parallels between clowning and gender, as well as their research and experiences. The text is the result of the first part ofan interview with the group in October 2021.
Keywords: Circo di SóLadies | Nem SóLadies; Feminisms; Feminist clowning; Gender studies